Pengaruh Motivasi Kerja dan Penggunaan Teknologi Informasi Terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Intervening pada CS Mart Pariaman - Muhammad Darrel Affitra; Muhammad Afuan; Chintya Ones Charli (Jurnal Ekonomi dan Bisnis Digital, 2026)
Human resources are one of the strategic assets of an organization that play a crucial role in supporting the successful achievement of organizational goals. This study aims to determine the extent of the effect of Work Motivation and the Use of Information Technology on Employee Performance, with Job Satisfaction as an Intervening Variable at CS Mart Pariaman. The method used is Structural Equation Modeling (SEM) analysis with Partial Least Squares (PLS), conducted by distributing questionnaires to 50 respondents. The results of the study show that: There is a significant effect of Work Motivation on Job Satisfaction at CS Mart Pariaman. There is no significant effect of the Use of Information Technology on Job Satisfaction at CS Mart Pariaman. There is a significant effect of Work Motivation on Employee Performance at CS Mart Pariaman. There is a significant effect of Job Satisfaction on Employee Performance at CS Mart Pariaman. Job Satisfaction mediates the effect of Work Motivation on Employee Performance at CS Mart Pariaman. Job Satisfaction does not mediate the effect of the Use of Information Technology on Employee Performance at CS Mart Pariaman.